Factor Influencing the Shear Strength Parameter - Kamaruzaman, Nur Arisya Fariha; Shahrizan, Nurul Syamina Afiqah; Ahmad, Ainatul Fasyeha; Mohd Razali, Siti Nooraiin (Multidisciplinary Applied Research and Innovation, 2022)
Many engineers confront with some issue when dealing with peat soil which is one of the problematic soils. Peat soil has a low value of shear strength and also would cause some problem in construction such as landslide and building fail. Many researchers have run test to increase the shear strength by manipulating the parameter of peat. The objectives in this study is to identify the factor that affecting the parameter of shear strength. The factor such as type of peat, moisture content, organic content, void ratio and pH value were discussed in this study. There were three steps used in this project to collect the data for factor influencing the shear strength parameter which are identification, screening and eligibility. Systematic literature review (SLR) method has been used in this project to collect the data and the results from previous study. This project has been through some process which is started from the process of identification to find the journals that related to the topic. The next step is process of screening which is to export the important data with suitable criteria and most related to this project. The last process of this project would be eligibility which is vital to achieve the objectives of this project. From the result, the effect of each peat parameters on shear strength could be observed. It can be seen that the type of peat would affect the value of shear strength. For example, hemis and fibric peat have a higher shear strength value than sapric peat. Other than that, it also can be concluded from the results that the values of shear strength decrease when moisture content, void ratio and pH values increase. Lastly, it can be observed from the result that value of friction angle decrease as the organic content increase.